Caracterização dos aspectos vocais de um coro infantojuvenil - Rosa, Milka Botaro; Prestes, Raquel; Margall, Soraya Abbes Clapes (CEFAC Saúde e Educação, 2014)
PURPOSE: to characterize the vocal health, knowledge of choristers in caring for her own voice, and perceptual analysis of the spoken voice, performed by an audiologist in a chorus children and youth. METHODS: the study included 20 individuals of both sexes, between 10 and 18 years, members of a choir, two questionnaires were applied: one facing parents on general health, medical and dietary habits, and another for the choristers facing experience in singing, knowledge of the voice and vocal health habits. Screening was performed for individual vocal perceptual analysis of the spoken voice. RESULTS: in the questionnaire back to the parents, it was observed that 40% of the choristers had some kind of allergy, whereas in the questionnaire aimed to choristers, 65% did not know how the voice is produced; carried out vocal training 100%, 80% did not care voice, 35% had vocal complaints; already screening vocal assessed that 35% expressed hoarse and breathy and rough 5%, the pitch was found predominantly acute (55%); articulation and resonance were balanced, the type was the predominant respiratory medium (65%), whereas the breathing mode mixed (45%), the coordination between breathing in 90%, the maximum phonation time increased by 65% and the coefficient s / z was adequate in 65%. CONCLUSION: the aspects of vocal health was observed a high rate of allergy, care of his own voice most choristers do not know how the voice is produced and auditory perception was found in a large number of choristers hoarse breathy vocal quality and maximum phonation time increased.

OBJETIVO: caracterizar os aspectos de saúde vocal, o conhecimento dos coristas quanto aos cuidados com a própria voz, e realizar uma análise percepto auditiva da voz falada, em um coro infanto juvenil. MÉTODOS: participaram deste estudo 20 indivíduos, de ambos os gêneros, entre 10 e 18 anos, integrantes de um coro. Foram aplicados dois questionários: um voltado aos pais sobre a saúde geral, tratamento médico e hábitos alimentares de seus filhos e outro para os coristas, que abordou aspectos sobre vivência no canto, conhecimentos sobre a voz, hábitos e saúde vocal. Foi realizada uma triagem vocal individual para análise perceptoauditiva da voz falada por meio de protocolo específico. RESULTADOS: no questionário aplicado aos pais, foi observado que 40% dos coristas apresentaram algum tipo de alergia. Quanto ao questionário respondido pelos coristas, 65% não souberam dizer como a voz é produzida; 100% realizavam aquecimento vocal; 80% não possuíam cuidados com a voz; 35% apresentaram queixa vocal. Na triagem vocal, verificou-se 35% de coristas com voz rouca e soprosa e 5% áspera; o pitch predominantemente agudo (55%); a articulação e a ressonância equilibradas; o tipo respiratório predominante foi o médio (65%); o modo respiratório misto (45%); a coordenação pneumofonoarticulatória presente em 90%; o tempo máximo fonatório aumentado em 65%; e o coeficiente s/z mostrou-se adequado em 65%. CONCLUSÃO: nos aspectos de saúde vocal, foi observado um alto índice de alergia; nos cuidados com a própria voz, a maioria dos coristas não sabe como a voz é produzida; na análise perceptoauditiva,foram encontrados em um grande número de coristas, qualidade vocal roucosoprosa e tempo máximo fonatório aumentado.
Characterization of the vocal aspects of a choir of children and teenagers
Keywords: Voz; Fonação; Qualidade da Voz; Música; Voice; Phonation; Voice Quality; Music